2011
DOI: 10.1097/sla.0b013e318211d7b5
|View full text |Cite
|
Sign up to set email alerts
|

Improving Postoperative Immune Status and Resistance to Cancer Metastasis

Abstract: Treatment aimed at perioperative enhancement of CMI and simultaneous inhibition of excessive catecholamine and prostaglandin responses, employing CpG-C, propranolol, and etodolac, could be successful in limiting postoperative immunosuppression and metastatic progression, more so than each treatment alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(98 citation statements)
references
References 0 publications
3
89
0
Order By: Relevance
“…Law et al. examined 1657 colorectal cancer patients 13 and found that postoperative complications were an independent factor associated with a worse overall survival (hazard ratio of 1.26) and a higher rate of overall recurrence (hazard ratio of 1.26). Similar hazard ratios were also reported in other studies 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Law et al. examined 1657 colorectal cancer patients 13 and found that postoperative complications were an independent factor associated with a worse overall survival (hazard ratio of 1.26) and a higher rate of overall recurrence (hazard ratio of 1.26). Similar hazard ratios were also reported in other studies 18.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the postoperative complications were risk factors for the survival or disease recurrence in various types of malignancies 7, 8, 9, 10, 11, 12. Furthermore, some authors have shown that the immunological response against postoperative complications enhanced the viability of undetectable residual tumor cells after surgery, thereby increasing the risk of disease recurrence 13, 14. However, despite numerous studies performed in patients with various types of malignancies, most previous studies have used and evaluated retrospectively collected data with relatively small sample sizes of less than 200 from a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…This index of LTR is highly sensitive to alterations in in vivo levels of NKCC. Specifically, NK cells were shown to create immunological synapses with MADB106 cells in the lungs [33], marginating pulmonary NK cells were shown to efficiently kill MADB106 cells [31, 34, 35], and selective in vivo depletion of NK cells decreased in vivo killing of MADB106 tumor cells, and increased MADB106 LTR and lung metastases by 20- to 200-fold [27, 36-40]. Most importantly, comparing effects of stress or of other in vivo manipulations between normal rats and rats that are temporarily depleted of NK cells in vivo (see Methods) distinguishes between effects that are mediated through alterations in NKCC and those that involve other or additional mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative NK-cell cytotoxic dysfunction has been demonstrated in preclinical [11, 2730] and clinical studies [11, 17, 29]. NK-cell functional impairment is associated with progressive metastatic disease in animal experimental models [4, 11, 31, 32]. In human patients with solid malignancies, inferior NK-cell function following surgery correlates with poor prognosis [3335].…”
Section: Mainmentioning
confidence: 99%
“…In human patients with solid malignancies, inferior NK-cell function following surgery correlates with poor prognosis [3335]. Even with the numerous reports documenting postoperative NK-cell suppression, very few studies have characterized the underlying mechanism of this impairment [4, 32, 36]. We provided the first in vivo evidence linking surgery to the metastasis of cancers via NK-cells through adoptive transfer of surgically stressed and control NK-cells into NK-deficient recipient mice, showing that surgically stressed NK-cells cannot protect from a lung tumor challenge.…”
Section: Mainmentioning
confidence: 99%